Penerapan Demonstrasi Mengasah Pahat Bubut pada Kompetensi Membubut dapat Meningkatkan Keterampilan Praktek Siswa Kelas X FL SMK Negeri 2 Karang Baru Aceh Tamiang - Novendri (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
ABSTRACT Novendri, 2022. "The application of the Lathe Chisel Sharpening Demonstration on turning competence can improve the practical skills of class X FL students at SMK Negeri 2 Karang Baru Aceh Tamiang". The skill of sharpening a lathe chisel or cutting tool (tool cutter) greatly affects the level of student learning/practice outcomes in the Lathe Practice lesson. At SMK Negeri 2 Karang Baru, there are still many students who have difficulty in sharpening Lathe chisels and cutting tools, this is indicated by the low average score of the Lathe Practice exam results. In addition, in the process of learning to read measuring instruments, and technical drawings are also not good. it is necessary to apply a demonstration method of presenting material, one of which is a demonstration of sharpening a lathe chisel/cutting tool (tool cutter). This study aims to improve the quality and learning outcomes of students in the practice of turning turning through the application of demonstrations of sharpening lathe chisels in class X Metal Fabrication Engineering (FL) SMK Negeri 2 Karang Baru. This type of research is classroom action research which is carried out in 2 cycles, each cycle consisting of planning, action, observation, and reflection stages. From the research that has been done, there is an increase in student learning mastery in each cycle, namely the first cycle of the first meeting (60%) and the second meeting (65%) of the second cycle of the first meeting (91%) and the second meeting (91%). This shows that the demonstration of sharpening a lathe chisel/tool ??cutter can improve lathe practice skills in lessons on doing work with a lathe in class X Metal Fabrication Engineering (FL) students in the even semester of SMK Negeri 2 Karang Baru Aceh Tamiang 2021/2022. Keywords: Lathe Chisel Sharpening Demonstration in Lathe Machine practice, tool cutter